2003
DOI: 10.2134/agronj2003.0233
|View full text |Cite
|
Sign up to set email alerts
|

Organic and Other Management Strategies with Two- and Four-Year Crop Rotations in Minnesota

Abstract: are many reasons for this, among them the development of effective fertilizers and pesticides, government poli-In the USA, the corn (Zea mays L.)-soybean [Glycine max (L.) cies, and favorable economics. Interest in developingMerr.] rotation depends on high levels of external inputs. Few research data exist comparing conventional production practices with practices alternatives to the present agricultural system has arisen involving reduced external inputs and expanded rotations. Two trials from a number of env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
96
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(111 citation statements)
references
References 2 publications
10
96
2
Order By: Relevance
“…Adjustment factors of 0.92, 0.92, and 0.83 were used to model crop yields from corn grain/silage, alfalfa, and soybeans, respectively, compared with conventional crop production (www.ers.usda.gov/Data/ARMS/app/Crop.aspx; ref. 40).…”
Section: Model 3 Dietary Guidelines For Americansmentioning
confidence: 99%
“…Adjustment factors of 0.92, 0.92, and 0.83 were used to model crop yields from corn grain/silage, alfalfa, and soybeans, respectively, compared with conventional crop production (www.ers.usda.gov/Data/ARMS/app/Crop.aspx; ref. 40).…”
Section: Model 3 Dietary Guidelines For Americansmentioning
confidence: 99%
“…Compared with conventional cropping systems, reduced yields were reported for most crops in organic systems 1,2,5,6 , whereas some organic systems produced equal or greater yields 3 . Yield differences between the two cropping systems are often crop specific.…”
Section: Introductionmentioning
confidence: 97%
“…Spurred on by concerns about increasing farm size, environmental pollution, reduced biodiversity across the landscape and increased consumer demand for organic products, investigators have reported on long-term studies of differences between conventional and organic cropping systems [1][2][3][4][5][6] , often with contradictory results. Compared with conventional cropping systems, reduced yields were reported for most crops in organic systems 1,2,5,6 , whereas some organic systems produced equal or greater yields 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The (Porter et al 2003). Two crop rotations and four management strategies are included in the trial, resulting in eight distinct crop management systems.…”
Section: The Variable Input Crop Management Systems (Vicms) Trial Lamentioning
confidence: 99%